2016
DOI: 10.7754/clin.lab.2016.160316
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Four Automated Urinalysis Systems Compared to Reference Methods

Abstract: The use of automated urinalysis demonstrated some weaknesses and should be checked by experienced laboratory staff using light microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Excellent agreement was not observed between any of the compared automated urine sediment analyzers and manual microscopy in this study. In previous studies, Enko et al reported that Cobas u701 showed substantial agreement for WBC and a fair agreement for RBC and EPI [37], and Bartosova et al found that IRIS Iq200 was nearly perfect regarding RBC evaluation [38]. This is not in full accordance with the results of our study, but the agreement for WBC in Cobas u701 (κ = 0.56) and the agreement for RBC in IRIS Iq200 (κ = 0.61) were proximately relevant to the previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…Excellent agreement was not observed between any of the compared automated urine sediment analyzers and manual microscopy in this study. In previous studies, Enko et al reported that Cobas u701 showed substantial agreement for WBC and a fair agreement for RBC and EPI [37], and Bartosova et al found that IRIS Iq200 was nearly perfect regarding RBC evaluation [38]. This is not in full accordance with the results of our study, but the agreement for WBC in Cobas u701 (κ = 0.56) and the agreement for RBC in IRIS Iq200 (κ = 0.61) were proximately relevant to the previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…When the urine occult blood test was negative and the RBC count was in normal range at the same time, it is possible to ignore the careful identification of unclassified cells images, especially for inexperienced staff. Confirmation of pathological results of the automated system by manual examination may be needed [7].…”
Section: Discussionmentioning
confidence: 99%
“…Digital flow morphology software is used to automatically isolate, characterize, and categorize urine particles, and on-screen verification allows user review and reclassification of particles when necessary. 4,5 The instrument is rapid and efficient, with each result being reported within 2 minutes of sample introduction to the Iris system. The following biologic elements were determined for this study: red blood cells, white blood cells, bacteria, budding yeast, yeast with pseudo hyphae, squamous epithelial cells, renal epithelial cells, mucus strands, sperm cells, cellular casts, and crystals.…”
Section: Specimen Analysesmentioning
confidence: 99%